Transformation of Regional Economic Performance in Indonesia During the COVID-19 Pandemic: A Comparative Analysis of GRDP from 2016 to 2023 - Hamzah, Muh. Qardawi; Syahrul; Muhammad, Fadhil (Journal of Institution and Sharia Finance, 2025)
The COVID-19 pandemic has caused significant disruptions to the global economy, including Indonesia, as reflected in the fluctuations of Gross Regional Domestic Product (GRDP) across various provinces. This study aims to analyze the differences in provincial GRDP in Indonesia between the pre-pandemic period and the pandemic period (2020–2023) in order to assess the impact of the pandemic on regional economic resilience. A comparative quantitative approach was employed, using the Wilcoxon Signed Rank Test on GRDP data based on constant prices, obtained from Statistics Indonesia (BPS). The analysis revealed a statistically significant difference in GRDP before and during the pandemic (p < 0.001), indicating a substantial economic shock. Sharp declines were particularly evident in provinces reliant on the tourism and manufacturing sectors, while provinces with more diversified economic structures or supported by agriculture exhibited relatively greater resilience. These findings highlight the importance of regional economic diversification and the strengthening of more resilient sectors as key strategies for confronting similar crises in the future.